2018
DOI: 10.4025/actasciagron.v41i1.39803
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing maps in the study of genetic diversity among irrigated rice genotypes

Abstract: This study presents self-organizing maps (SOM) as an alternative method to evaluate genetic diversity in plant breeding programs. Twenty-five genotypes were evaluated in two environments for 11 phenotypic traits. The genotypes were clustered according to the SOM technique, with variable topology and numbers of neurons. In addition to the SOM analysis, unweighted pair group method with arithmetic mean clustering (UPGMA) was performed to observe the behavior of the clustering when submitted to these techniques a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Result concordant with the study by Silva et al (2019). The estimated coefficients of variation for the characteristic were compatible with those obtained in other rice studies (Costa et al, 2002;Hosan et al, 2010;Silva et al, 2011;Streck et al, 2017;Santos et al, 2019;, emphasizing the acceptable test quality.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Result concordant with the study by Silva et al (2019). The estimated coefficients of variation for the characteristic were compatible with those obtained in other rice studies (Costa et al, 2002;Hosan et al, 2010;Silva et al, 2011;Streck et al, 2017;Santos et al, 2019;, emphasizing the acceptable test quality.…”
Section: Resultssupporting
confidence: 90%
“…Rice (Oryza sativa) is one of the most consumed cereals in the world, characterizing it as main source of basic food (Walter et al, 2008;Santos et al, 2019;Silva et al, 2019) for more than half the world population (Irgsp, 2005;Jacquemin et al, 2013;Zhang et al, 2013;Muthayya et al, 2014). Thus, it has great potential to reduce food insecurity (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In complex scenarios such as this in which the genetic similarity between genotypes can differ (siblings, half siblings, parents and grandparents), the SOM method allows the visualization of patterns of similarity and data classification based on the distances between genotypes 29 . This method is efficient, as noted by [30][31][32] . Thus, the agreement between most of the applied techniques, especially between the K-means and SOM methods, suggested that the Asiatic clones were best represented as two clusters, as were the IAC 400 series.…”
Section: Discussionmentioning
confidence: 99%
“…KSOMs are an unsupervised learning neural network method that detects similarities between entry patterns through a competition process [ 25 , 49 , 50 ]. The value of each individual assessed for the 31 traits in each environment was used as an input.…”
Section: Methodsmentioning
confidence: 99%